2022
DOI: 10.35631/jthem.729014
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the Satisfaction of Tourists Visiting Mabul Island as a Tourist Destination Based on Demographic Factors

Abstract: The study aims to examine whether the satisfaction of the tourists in visiting Mabul Island as a tourist destination can be influence by demographic variables. The study involves primary data collection where questionnaire was used as the instrument to collect information. The questionnaire was distributed both physically in the island and also through Google Form. The questionnaire was distributed to 169 respondents selected through nonprobability sampling, purposive sampling method. The questionnaire was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Regarding the age of the tourists, the results revealed no significant differences between age groups in terms of their satisfaction with the experience and their behavioral intentions. These findings were consistent with Geetha et al [76] and Lu et al [74]. Despite there being no significant differences, it could be observed that for experiential quality, there were significant differences between the age groups regarding tourists' ratings of the fact that the tourism experience allowed them to escape from their daily routine.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the age of the tourists, the results revealed no significant differences between age groups in terms of their satisfaction with the experience and their behavioral intentions. These findings were consistent with Geetha et al [76] and Lu et al [74]. Despite there being no significant differences, it could be observed that for experiential quality, there were significant differences between the age groups regarding tourists' ratings of the fact that the tourism experience allowed them to escape from their daily routine.…”
Section: Discussionsupporting
confidence: 90%